2012
DOI: 10.1095/biolreprod.111.092510
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Poliovirus Receptor, Erythrocyte Protein Band 4.1-Like 3, Regulator of G-Protein Signaling 11, and Oxytocin Receptor in Mouse Ovarian Cells During Follicle Growth and Early Luteinization In Vitro and In Vivo1

Abstract: Poliovirus receptor (Pvr), erythrocyte protein band 4.1-like 3 (Epb4.1l3), regulator of G-protein signaling 11 (Rgs11), and oxytocin receptor (Oxtr) expression were quantified in in vitro- and in vivo-grown mouse follicles. The expression of all genes was increased during antral growth in in vitro-grown cumulus cells, whereas only Rgs11 and Oxtr were increased and Pvr and Epb4.1l3 were decreased in in vivo grown cumulus cells. In vivo mural granulosa cells showed the highest expression of Pvr, Rgs11, and Oxtr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…This may confirm the findings that a family member of CAMK1D, CAMK4, can increase the CYP11A1 expression in granulosa-luteal cells (20). The role of the three most promising genes in pregnancy prediction might be studied in an in vitro model (37), allowing observation and regulation during the follicular growth and post-LH phases.…”
Section: Discussionsupporting
confidence: 76%
“…This may confirm the findings that a family member of CAMK1D, CAMK4, can increase the CYP11A1 expression in granulosa-luteal cells (20). The role of the three most promising genes in pregnancy prediction might be studied in an in vitro model (37), allowing observation and regulation during the follicular growth and post-LH phases.…”
Section: Discussionsupporting
confidence: 76%
“…In vitro growth of follicles isolated from cryopreserved ovarian tissue, followed by in vitro maturation to produce oocytes competent for fertilization and implantation, is an active area of investigation for cancer patients (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Thus far, successful live birth has been achieved in murine models (23), and the technology is being optimized in nonhuman primates (19,(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…All three genes were not affected by gonadotropins. Absence of significant Oxtr, Pgr, and Egfr expression induction indicated that mural cells did not express early signs of luteinization (Fujinaga et al 1994, Clemens et al 1998, Segers et al 2012, which was reinforced by the endocrine profile on day 9.…”
Section: Lhcgr Expression In the Acute And Chronic Phasementioning
confidence: 97%
“…35 pM rhCG, or 25 mIU/ml HP-hMG ('Menopur', Ferring). The 10 mIU/ml rFSH condition is a continuation of the minimal effective dose of FSH needed in culture (Adriaens et al 2004, Segers et al 2012. The 25 mIU/ml rFSH condition is considered 'slightly supraphysiological' in accordance with the supraphysiological FSH injections in assisted reproductive technologies (ART) patients .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation